GIS in development control process : the case of development control system for city hall of Kuala Lumpur - Johar, Foziah (Faculty of Built Environment, 2007)
Development control involves a complex process and tedious procedures. The due consideration given to an application for planning requires a tedious process, as it will have to go through several committees and technical evaluations. Generally, a planning application will be assessed in terms of current development scenario, land information, planning requirements and planning design. Development control and approval, which involves the process of analyzing the appropriateness of planning applications, requires various data from the relevant agencies. Apparently, an information system is necessary not only to keep and display data pertaining to planning application for the purpose of administrative functions but should also be designed to facilitate planning at strategic level. The step taken by the Urban Planning Department (JPRB), City Hall of Kuala Lumpur (CHKL) through the development of an integrated development control system is seen as an innovative approach to urban planning. The system was designed to cover all the necessary work process involved in development control and approval supported by Geographical Information System (GIS) application. The developed system which integrates seven sub systems including planning authorization, building control, enforcement, geospatial and planning information, information kiosk, meeting presentation and documentation processing, incorporates the use of GIS for planning and monitoring purposes. With its powerful capacity for spatial data management, spatial analysis, and visualization, GIS provides planners with tools to implement their work more efficiently especially with support of the interactive and user-friendly interface developed to ease the use of the sophisticated system without the need of advanced technical skill. The system will be able to support planning and decisionmaking because it offers relatively quick response to analytical questions and monitoring issues. This paper will explain GIS application in Development Control System by CHKL as well as benefits and drawback of the system.